The Importance of eWOM Elements on Online Repurchase Intention: Roles of Trust and Perceived Usefulness - Maduretno, Raden Bernard Eka Hutomo Putra; Junaedi, Sheellyana (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
The purpose of this research is to determine the effect of online review elements, including electronic Word of Mouth (eWOM) quantity, credibility, and quality, on customer’s online repurchase intention through the mediating roles of online seller trust and perceived usefulness of the website. A partial least square (PLS) based structural equation modeling (SEM) was chosen to evaluate the measurement of research constructs and test the research hypotheses. This research uses data collected through online questionnaires in Yogyakarta, Indonesia. The respondents’ criterion was college students who had read online recommendations before making purchases on Bukalapak.com, an e-commerce platform in Indonesia. The results suggest that the credibility and quality of eWOM have a positive direct effect on consumers’ repurchase intention, while the eWOM quantity has a negative influence on repurchase intentions. The eWOM credibility and quality indirectly influence repurchase intentions through trust in the online vendor. The perceived usefulness of the websiteonly mediates the influence of eWOM quality on online repurchase intention. Limitations and further research were also discussed.